Euro Area Monetary Policy in Uncharted Waters - Stavrev, Emil (IMF Working Papers; Working Paper ;, 2009)
We analyze the European Central Bank's (ECB's) response to the global financial crisis. Our results suggest that even during the crisis, the core part of ECB's monetary policy transmission-from policy rates to market rates-has continued to operate, but at a decreased efficiency. We also find some evidence that the ECB's non-standard measures, namely the lengthening of the maturity of monetary policy operations and the provision of funds at the fixed rate, reduced money market term spreads, facilitating the pass-through from policy to market rates. Furthermore, the results imply that the substantial increase in the ECB's balance sheet may have contributed to a reduction in government bond term spreads.